Actual problems of studying of economic theory at higher educational establishments - Kundeyeva, Galina; Cherednichenko, Galina (My University, 2011)
The authors disclosed the main features of the teaching and studying of economic theory at the higher educational establishments. They determined the principal theoretical issues which must be tied to the practice of modern economic entities.
Keywords: economic theory; економічна теорія; вивчення дисципліни; study of the discipline; кафедра ділової іноземної мови та міжнародної комунікації; кафедра економічної теорії